Transformation of the Australian public sector and environmental accounting practices: the case of water in 2001 - David R. Moore (Australasian Accounting, Business and Finance Journal, 2008)
This paper analyses a case study undertaken in 2001 of a Victorian public sector water utility to examine the implications of public sector ‘modernisation’ reforms of the 1980s and 1990s for the adoption of environmental accounting (EA) procedures within the Victorian water industry. Legislative reforms have resulted in the allocation of overhead costs for the purpose of segmented reporting and to measure the ‘full cost’ of departments. This was consistent with the “managerialist”, “marketization” and “strategic” phases of public sector ‘modernisation’ reforms, but did not measure the full economic (environmental) cost. The application of full cost recovery for the purpose of efficiency was further evidence of the impact of public sector modernisation reforms but did not extend to the recovery of externalities. Private environmental costs were traced and integrated into direct cost categories, consistent with the philosophy of managerialism. Costs were measured for the purposes of promoting the contracting out of selected services and functions. There was limited adoption of environmental accounting practices, due to the absence of environmental accounting measurement guidelines. Staff interviewed recognized the importance of environmental issues, but were yet to appreciate the benefits of adopting EA practices. Subsequent to the case study, the Victorian government introduced legislation that required water authorities to make provisions for environmental contributions, a step towards accounting for environmental externalities. This was the beginning of the “sustainability” phase of public sector ‘modernisation’ reforms.
Keywords: New Public Management; Australian public sector reform; Water industry; Managerialism; Cost Recovery; Externalities; Environmental Accounting.